Isolation and characterization of antibiotic from endophyte of melastome malabathricum L. in Kuching area - Jane, Sebestian Taka (Universiti Malaysia Sarawak, UNIMAS, 2010)
A study was done to determine the presence of antimicrobial substances in endophytic fungal isolates from Melastoma malabathricum L. plants. Twelve isolates of endophytes, designated as SB1, SB2, SB3, ST1.1, ST1.2, ST1.3, ST1.4, SP1.1, SP1.2, SP1.3, SP1.4 and SM1.1, were obtained from plant samples collected from four different locations in Kuching area, which were BDC area, Tabuan area, Pending area and Matang area. Preliminary screening for antimicrobial activities using fungal colonies revealed that only three, SB1.1, ST1.3 and SP1.1 were active against all test bacteria consisted of Gram positive bacteria, namely Staphylococcus aureus, and Gram negative bacteria, namely Escherichia coli, Salmonella typhi and Enterobacter aerogenes. Subsequently, for further screening using overlay agar technique, endophytes which showed positive antimicrobial activities in preliminary screening was used. In the test, only isolates ST1.3 was active against all test bacteria, while isolates SP1.1 active only against three test bacteria, except Staphylococcus aureus. Further study using methanol extract of isolates ST1.3 and SP1.1 was carried out using agar disc diffusion method. Methanol extract of isolates ST1.3 showed positive antimicrobial activities against Staphylococcus aureus and Enterobacter aerogenes, and no positive antimicrobial activities showed for methanol extract of isolates SP1.1. The minimal inhibitory concentration (MIC) of methanol extract of isolates ST1.3 that inhibited both test bacteria was 50mg/ml. Macroscopic observations for determination of the morphological characteristics of the endophytes showed that, isolates ST1.3 colonies have dark, asexual spores and having the septate mycelium. While isolates SP1.1 colonies have white colonies, not forming spore and having the septate mycelium. Hence, isolates ST1.3 and SP1.1 were tentatively identified as Aspergillus sp and Geotrichum sp respectively.